Does anyone know if this function has a name? I came up with it by looking at the power series for $e^z$, changing the summation to an integral, and substituting the gamma function for the factorial function.

  • 5
    $\begingroup$ +1 cuz you've got me curious too. Also is x supposed to be real? and if so is there a reason you restricted its domain to the reals? $\endgroup$ – Thoth Jun 15 '12 at 5:26
  • 2
    $\begingroup$ I just found the following, which is related to its value at 1: en.wikipedia.org/wiki/Frans%C3%A9n%E2%80%93Robinson_constant $\endgroup$ – mlbaker Jun 15 '12 at 6:08
  • 3
    $\begingroup$ I think it is Ramanujan's formula, i.e.: $$\int\limits_{0}^{\infty}\frac{z^{t} \, dt}{\Gamma(1+t)}=e^{z}-\int\limits_{0}^{\infty}\frac{e^{-z\tau}d\tau}{\tau(\ln^2 (\tau)+\pi^{2})},\,\,\, Re(z)\ge{0}$$ $\endgroup$ – qoqosz Jun 17 '12 at 9:05
  • 2
    $\begingroup$ @mlbaker I recalled this equation from one of my bookmarks: artofproblemsolving.com/Forum/viewtopic.php?p=1226810#p1226810 . I also found another source which you may find useful: Erdelyi, A., et al., Higher Transcendental Functions, vol 3. You can find it online at apps.nrbook.com/bateman/Vol3.pdf To be more specific look at the page 217 where author introduces your integral and denotes it by $\nu (x)$. It may be a good place to start looking for other references I guess. $\endgroup$ – qoqosz Jun 17 '12 at 19:21
  • 1
    $\begingroup$ @mlbaker: This may be a "troll function," as you call it, but it is pretty interesting nonetheless! $\endgroup$ – user26872 Jun 18 '12 at 18:46

Almost tautological, but we can also find that

$$ f(x) = e^{x} \left( 1 - \int_{0}^{1} \frac{\Gamma(s, x)}{\Gamma(s)} \; ds \right),$$

where $\Gamma(s, x) = \int_{x}^{\infty} t^{s-1}e^{-t} \; dt$ is the incomplete gamma function. Indeed,

$$ f'(x) = \int_{0}^{\infty} \frac{s x^{s-1}}{\Gamma(s+1)} \; ds = \int_{0}^{1} \frac{x^{s-1}}{\Gamma(s)} \; ds + f(x)$$

and thus

$$ (f(x)e^{-x})' = \int_{0}^{1} \frac{x^{s-1}e^{-x}}{\Gamma(s)} \; ds.$$

Then integrating both sides with respect to $x$ gives the desired relation.

Now we try to find its asymptotic formula. Since $\Gamma(s,x) / \Gamma(s) \searrow 0$ as $x \to \infty$, we find

$$f(x) = (1 - o(1))e^{x}$$

asymptotically. To obtain a better approximation, note that $1/\Gamma(s) \asymp s$ near $s = 0$. Thus

$$ \begin{align*} \int_{0}^{1} \frac{\Gamma(s, x)}{\Gamma(s)} \; ds &\asymp \int_{0}^{1} s\Gamma(s, x) \; ds \\ &= \int_{0}^{1} (\Gamma(s+1,x) - x^{s}e^{-x}) \; ds \\ &= \int_{0}^{1} \int_{x}^{\infty} t^{s}e^{-t} \; dt ds - \frac{x-1}{\log x}e^{-x} \\ &= \int_{x}^{\infty} \left( \frac{t-1}{\log t}\right) e^{-t} \; dt - \frac{x-1}{\log x}e^{-x} \\ &= \int_{x}^{\infty} \left( \frac{t-1}{\log t}\right)' e^{-t} \; dt \\ &\asymp \int_{x}^{\infty} \frac{e^{-t}}{\log t} \; dt \\ &\asymp \frac{e^{-x}}{\log x}. \end{align*}$$

In particular, we have

$$f(x) = e^{x} - O\left( \frac{1}{\log x} \right).$$

  • $\begingroup$ +1. Nice one! I didn't expect one could find a really good asymptotic like this! $\endgroup$ – user17762 Jun 15 '12 at 7:34

Laplace transform

We consider the function for $x\ge 0$. As found by @Mathlover, it is not hard to get the Laplace transform of $f(x)$. Inverting, we find $$f(x) = \frac{1}{2\pi i} \int_\gamma ds\, e^{s x}\frac{1}{s\log s},$$ where $\gamma$ is the Bromwich contour. There is a singularity at $s=1$ and a cut from $s=0\to -\infty$. We deform the contour in the usual way and simplify, with the result $$\begin{eqnarray*} f(x) &=& e^x - \int_0^\infty d\rho\, \frac{e^{-\rho x}}{\rho(\log^2\rho + \pi^2)} \\ &=& e^x - \int_{-\infty}^\infty d\sigma\, \frac{e^{-x e^\sigma}}{\sigma^2 + \pi^2}. \end{eqnarray*}$$ It is possible to go further with the last integral, but we'll stop here.

Addendum: Series

Let's examine the series for $f(x)$. Define $$\begin{eqnarray*} \Delta(x) &=& \int_0^\infty d\sigma\, \frac{e^{-x e^\sigma} + e^{-x e^{-\sigma}}}{\sigma^2 + \pi^2} \end{eqnarray*}$$ Note that $f(x) = e^x - \Delta(x)$. We have $e^{-x e^\sigma} + e^{-x e^{-\sigma}} \le e^{-x}+1$, and $\int_0^\infty d\sigma\, \frac{1}{\sigma^2+\pi^2}$ converges, so $\Delta(x)$ converges uniformly.

Clearly the derivative of $\Delta(x)$ doesn't exist at $x=0$ (the integral $\int_0^\infty d\sigma\,\frac{\cosh \sigma}{\sigma^2+\pi^2}$ diverges) so there is no Maclaurin series for $f(x)$. We can do a Taylor series about any $x>0$. Of course, we must evaluate integrals of the form $$\left.\frac{d^k}{d x^k} \Delta(x)\right|_{x=x_0} = (-1)^k \int_0^\infty d\sigma\, \frac{e^{k\sigma -x_0 e^\sigma} + e^{-k\sigma -x_0 e^{-\sigma}}}{\sigma^2 + \pi^2}.$$ These integrals are uniformly convergent for $x_0 >0$. In this regard it is useful to notice that $e^{-k\sigma -x_0 e^{-\sigma}} \le 1$ and $$e^{k\sigma -x_0 e^\sigma} \le \begin{cases} e^{-x_0}, & x_0 \ge k \\ \left(\frac{k}{x_0 e}\right)^k, & \mathrm{else}. \end{cases}$$ For large $x_0$ the dominant terms in the expansion come from the series for $e^x$, as expected.

Trapezoidal rule

Approximate the integral by a sum. Let the step size be $1/m$, where $m=1,2,\ldots$, and let $g_k = \frac{x^{k/m}}{\Gamma(k/m+1)}$. Then, $$\begin{eqnarray*} \int_0^\infty dt\, \frac{x^t}{\Gamma(t+1)} &\simeq& \lim_{n\to\infty} \left( \frac{1}{m}\sum_{k=0}^n g_k -\frac{1}{2m}(g_0+g_n) \right)\\ &=& \frac{1}{m}E_{1/m}(x^{1/m}) -\frac{1}{2m} \\ &=& \frac{1}{m} e^x\left(1+\sum_{k=1}^{m-1}\frac{\gamma(1-k/m,x)}{\Gamma(1-k/m)}\right) - \frac{1}{2m}, \end{eqnarray*}$$ where $E_\alpha(z)$ is the Mittag-Leffler function and $\gamma$ is the lower incomplete gamma function. (The relation for $E_{1/m}(x^{1/m})$ used above can be found in this paper.)

In the limit $m\to\infty$ the sum is equal to the original integral, so $$\begin{eqnarray*} f(x) &=& e^x \lim_{m\to\infty} \frac{1}{m} \sum_{k=1}^{m-1}\frac{\gamma(1-k/m,x)}{\Gamma(1-k/m)} \\ &=& e^x \int_0^1 ds\,\frac{\gamma(s,x)}{\Gamma(s)} \end{eqnarray*}$$ This is the integral formula found by @sos440 using another method.

Here are the sums for $m=1$ and $2$. $$\begin{array}{ll} m & f(x) \\ \hline 1 & e^x - 1/2 \\ 2 & \frac{1}{2}e^x \left(\mathrm{erf}\left(\sqrt{x}\right) + 1\right) -\frac{1}{4} \end{array}$$ Since $f(x) \simeq e^x-1/2$, $f^{-1}(x)\simeq \log(x+1/2)$.

Below we plot $f(x)$ (solid), $e^x$ (dashed, black), and the approximations for $m=1$ (dashed, red), and $m=2$ (dashed, blue).

m = 1

m = 2


This is a bit too long for a comment.

I don't think the function has any specific name. One plausible reason why this function doesn't have its own name is probably because it's growth is very closely related to $\exp(x)$ as expected. A very rough analysis as shown below gives some growth of this function with respect to $x$. The argument can be improved to get better growth rates of the function.

If we let $n = \lfloor t \rfloor$, then $$(n+1)! = \Gamma(n+2) \geq \Gamma(t+1) \geq \Gamma(n+1) = n!$$ Hence for $t \in [n,n+1)$, assuming $x>0$, $$\dfrac{x^t}{(n+1)!} \leq \dfrac{x^{t}}{\Gamma(t+1)} \leq \dfrac{x^t}{n!}$$ Now $$\int_0^{\infty} \dfrac{x^t}{\Gamma(t+1)} dt = \sum_{n=0}^{\infty} \int_n^{n+1} \dfrac{x^t}{\Gamma(t+1)} dt$$ Hence, $$\sum_{n=0}^{\infty} \int_n^{n+1} \dfrac{x^t}{(n+1)!} dt \leq \int_0^{\infty} \dfrac{x^t}{\Gamma(t+1)} dt \leq \sum_{n=0}^{\infty} \int_n^{n+1} \dfrac{x^t}{n!} dt$$ $$\sum_{n=0}^{\infty} \dfrac{x^{n+1}-x^n}{(n+1)! \log(x)} \leq \int_0^{\infty} \dfrac{x^t}{\Gamma(t+1)} dt \leq \sum_{n=0}^{\infty} \dfrac{x^{n+1}-x^n}{n! \log(x)}$$ $$\dfrac{(x-1)}{\log(x)} \left(\sum_{n=0}^{\infty} \dfrac{x^n}{(n+1)!} \right) \leq \int_0^{\infty} \dfrac{x^t}{\Gamma(t+1)} dt \leq \dfrac{(x-1)}{\log(x)} \left(\sum_{n=0}^{\infty} \dfrac{x^n}{n!} \right)$$ $$\dfrac{(x-1)}{\log(x)} \dfrac{\exp(x)-1}{x} \leq \int_0^{\infty} \dfrac{x^t}{\Gamma(t+1)} dt \leq \dfrac{(x-1)}{\log(x)} \exp(x)$$


$$f(x) = \int_0^\infty \frac{x^t}{\Gamma(t+1)} \, dt$$

I have noticed that we can find Laplace transform of this function in closed form. You can define the function as inverse Laplace Transform in closed form.

$$ {\mathcal L}\left\{ {x^t} \right\}(s)=\int_0^\infty x^t e^{-sx} \, dx=\frac{\Gamma(t+1)}{s^{t+1}}$$

$$ {\mathcal L}\left\{ {f(x)} \right\}(s)=\int_0^\infty \frac{1}{\Gamma(t+1)}\int_0^\infty x^t e^{-sx} \, dx \, dt=\int_0^\infty \frac{1}{s^{t+1}} \, dt=\frac{1}{s}\int_0^\infty s^{-t} \, dt=\frac{1}{s\ln{s}}$$

UPDATE: I am trying to find a method to define the function as series as well . I am going to post if I find a way in series methods.

My starting point for series methods:.

$$ {\mathcal L}\left\{ {f(x)e^{-x}} \right\}(s)=\frac{1}{(s+1)\ln{(s+1)}}$$

  • $\begingroup$ I think the logarithm should be placed at the denominator. $\endgroup$ – Sangchul Lee Jun 15 '12 at 10:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.